2009
DOI: 10.1080/13693780903164566
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency opsonin-independent phagocytosis of Candida parapsilosis by human neutrophils

Abstract: Candida species are associated with invasive fungal infections, and C. parapsilosis has become increasingly prevalent. As key antifungal effector cells, the function of human neutrophils confronting C. parapsilosis was investigated. We hypothesized that interaction between neutrophils and Candida species may not be uniform. Opsonins were omitted from these studies to understand the antifungal mechanisms at their most basic level. Human neutrophils underwent phagocytosis of C. parapsilosis with much higher effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
1
23
1
Order By: Relevance
“…Human neutrophils underwent phagocytosis and killing of C. parapsilosis much more efficiently than C. albicans yeast, suggesting that these interactions have properties that are unique among different Candida spp. [82]. Despite the increased susceptibility of preterm neonates to infection with C. parapsilosis , neutrophils from these patients responded to Candida in a similar fashion to adult cells [83].…”
Section: Host Defensementioning
confidence: 99%
See 2 more Smart Citations
“…Human neutrophils underwent phagocytosis and killing of C. parapsilosis much more efficiently than C. albicans yeast, suggesting that these interactions have properties that are unique among different Candida spp. [82]. Despite the increased susceptibility of preterm neonates to infection with C. parapsilosis , neutrophils from these patients responded to Candida in a similar fashion to adult cells [83].…”
Section: Host Defensementioning
confidence: 99%
“…Neutrophil phagocytosis of C. albicans is mediated in part via β-glucan recognition by dectin-1 and complement receptor 3 [8487], although there is an ongoing controversy about the contribution of each receptor. Neutrophil phagocytosis of C. parapsilosis , however, does not appear to be mediated by dectin-1 or complement receptor 3, as neutrophil treatment with blocking antibodies against both receptors did not inhibit phagocytosis [82]. Current work from our group has demonstrated that the lectin galectin-3 plays an important role in the increased efficiency of neutrophil phagocytosis of C. parapsilosis versus C. albicans [Linden et al ., The role of galectin-3 in the human neutrophil response to candida and protection against disseminated candidiasis (2012), Submitted].…”
Section: Host Defensementioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that Dectin1 −/− mice were more susceptible to disseminated C. tropicalis infection than WT mice [22]. Little is known about whether dectin-1 participates in immunity to other NAC species, although phagocytosis of C. parapsilosis by neutrophils was not impaired following dectin-1 blockade in vitro [40]. Similarly, no difference in binding of C. glabrata was detected between WT and dectin-1 −/− bone marrow macrophages [41].…”
Section: Pattern Recognitionmentioning
confidence: 99%
“…Several NAC species appear to be killed more efficiently than C. albicans [40, 8587]. For example, killing of C. tropicalis , C. parapsilosis , C. krusei and C. glabrata by human neutrophils was higher than C. albicans killing [85, 86].…”
Section: Cellular Immunity To Candida Species: the First Line Of Defensementioning
confidence: 99%